MOBILE LEARNING APPLICATIONS AND CHANGES IN MATERNAL BEHAVIOR IN THE PROVISION OF FOOD FOR CHILDREN: SYSTEMATIC REVIEW - Wibowo, Daniel Akbar; Dewi, Yulia Lanti Retno; Hikmayani, Nur Hafidha; Zen, Dini Nurbaeti (South Eastern European Journal of Public Health, 2024)
Background: Nutritional problems among children, especially in developing countries, remain a significant concern. Stunting, underweight, and malnutrition are prevalent due to inadequate dietary intake and poor maternal education. Mobile learning (m-learning) applications have emerged as potential tools to enhance maternal knowledge and improve child nutrition. This study systematically reviews existing literature to assess the impact of m-learning applications on changing maternal behavior in the provision of food for children. Method: This systematic literature review follows the PRISMA guidelines. The review was conducted in August 2024, covering studies published from 2014 to 2024. Databases including Scopus, PubMed, and Crossref were searched using relevant keywords. A total of 348 articles were identified, with 30 meeting the inclusion criteria for final analysis. The selected studies were analyzed to evaluate the effectiveness of m-learning applications in altering maternal behavior related to food provision. Results: The review indicates that m-learning applications significantly enhance maternal knowledge and positively influence food provision behaviors. However, the effectiveness of these applications is influenced by factors such as socio-economic status, cultural context, and the usability of the application. Personalized feedback, community support, and interactive features within the applications are crucial for achieving behavior change. Conclusions: M-learning applications hold substantial potential for improving maternal behavior in food provision, thereby enhancing child nutrition. Future developments should focus on culturally relevant content, user-friendly interfaces, and integrating community support mechanisms to maximize the effectiveness of these interventions.